Representation of Children's Education Through Extracurricular Batik Activities at SDN 1 Soditan, Lasem District, Rembang Regency - Rahmadani, Eria Natifa; Fardani, Much Arsyad; Fajrie, Nur (PT FORMOSA CENDEKIA GLOBAL, 2024)
This qualitative research examines the representation of children's education through batik extracurricular activities at SDN 1 Soditan, Lasem. The aim of this research is to analyze how the batik extracurricular at SDN 1 Soditan, Lasem represents children's education in the aspects of technical skills, cultural understanding, character development and preserving local traditions. Case study research was conducted during June-July 2024, involving teachers and students. The results show that the program has been implemented effectively, but is still focused on the technical aspects of batik making. A deep understanding of the history and philosophy of Lasem batik, including Javanese-Chinese cultural acculturation, has not been fully achieved. However , these activities can improve crucial interpersonal skills, strengthen awareness of cultural identity, and foster pride in the richness of local traditions. This program is also effective in teaching universal values such as respect for diversity. Overall, batik extracurricular activities have proven to be an effective means for character education, cultural preservation, and the development of students' holistic skills.